The Marketing Of Ornamental Fish at Business Groups Diamond Fish Club in Tampan Village Payung Sekaki Subsdistrict Pekanbaru City Riau Province - Mindo Prayudha; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in October 2016 which located in Tampan Village Payung Sekaki Subsdistrict Pekanbaru City Riau Province. This study was to identify the marketing conditions ornamental fish inside and outside of local and system marketing in expand the marketing in the diamond fish club. Methods used in this research is a method of survey with 8 respondents determinatied by the census. The result showed that marketing ornamental fish in the done at retail and packages, while marketing ornamental fish in other regions be done in pacages. Cost of, quarantine and risk of death ornamental fish borne of the cultivator (members of the group). Sales in the package fish addressed to cultivator of the and traders retailer, while retail are more dominant to individuals. The expansion of the marketing done by means of join the contest, recruiting members from outside, training and cooperation.Keywords: marketing, ornamental fish, Diamond Fish Club